Analysis of oxygen‐17 excess of nitrate and sulfate at sub‐micromole levels using the pyrolysis method. (1st October 2013) - Geng, Lei; Schauer, Andrew J.; Kunasek, Shelley A.; Sofen, Eric D.; Erbland, Joseph; Savarino, Joël; Allman, Daniel J.; Sletten, Ronald S.; Alexander, Becky
<x xml:space="preserve">Abstract</x> RATIONALE The oxygen‐17 excess (Δ17O) of nitrate and sulfate contains valuable information regarding their atmospheric formation pathways. However, the current pyrolysis method to measure Δ17O requires large sample amounts (>4 µmol for nitrate and >1 µmol for sulfate). We present a new approach employing a Gas Bench interface which cryofocuses O2 produced from sample pyrolysis, enabling the analysis of sub‐micromole size samples. METHODS Silver nitrate or sulfate at sub‐micromole levels in a sample container was thermally decomposed to O2 and byproducts in a modified Temperature Conversion/Elemental Analyzer (TC/EA). Byproducts (mainly NO2 for silver nitrate and SO2 for silver sulfate) were removed in a liquid nitrogen trap and the sample O2 was carried by ultra‐pure helium (He) gas to a Gas Bench II interface where it was cryofocused prior to entering an isotope ratio mass spectrometer. RESULTS Analysis of the international nitrate reference material USGS35 (Δ17O = 21.6‰) within the size range of 300–1000 nmol O2 gave a mean Δ17O value of (21.6 ± 0.69) ‰ (mean ±1σ). Three inter‐laboratory calibrated sulfate reference materials, Sulf‐α, Sulf‐β and Sulf‐ε, each within the size range of 180–1000 nmol O2, were analyzed and shown to possess mean Δ17O values of (0.9 ± 0.10) ‰, (2.1 ± 0.25) ‰ and (7.0 ± 0.63) ‰, respectively. CONCLUSIONS The analyses of nitrate and sulfate reference materials at sub‐micromole levels gave Δ17O values consistent with their accepted values. This new approach of employing the Gas Bench to cryofocus O2 after the pyrolysis of AgNO3 and Ag2SO4 particularly benefits the effort of measuring Δ17O in sample types with a low abundance of nitrate and sulfate such as ice cores. Copyright © 2013 John Wiley & Sons, Ltd.